2014
DOI: 10.1186/1471-2458-14-1071
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to children’s caries: a structural equation modeling approach

Abstract: BackgroundDental caries among preschool children is highly prevalent in many less-developed countries.MethodsA model which explored the factors related to children’s dental caries was tested in this study using structural equation modeling. Caregivers of children aged 5 years were surveyed on their socioeconomic status, and their oral health knowledge, attitudes and practices. In addition, information on their children’s oral health practices, dental insurance and dental service utilization were collected. Exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 16 publications
3
34
0
1
Order By: Relevance
“…In this study, the caregiver’s social support was not significantly associated with a child’s frequency of sugary snack intake. The frequency of sugary snack intake by children was predominantly related to the caregiver’s frequency of sugary snack intake and other factors, which was also shown in our previous study [16, 22]. In addition, these findings revealed that a child’s sugary snack intake habits are influenced by his/her caregiver’s sugary snack intake habits.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, the caregiver’s social support was not significantly associated with a child’s frequency of sugary snack intake. The frequency of sugary snack intake by children was predominantly related to the caregiver’s frequency of sugary snack intake and other factors, which was also shown in our previous study [16, 22]. In addition, these findings revealed that a child’s sugary snack intake habits are influenced by his/her caregiver’s sugary snack intake habits.…”
Section: Discussionsupporting
confidence: 85%
“…The Knowledge, Attitude and Practice (KAP) survey model offers a conceptual framework for analyzing human behavior and its effects on choices or interventions by characterizing knowledge, feelings, and actions [20]. The model considers the importance of an individual's knowledge and attitude in influencing behavior change [21,22]. It also recognizes the impact of external factors, such as socioeconomic and environmental influences, on individual behavior [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…ANN was able to detect the most important and least important predictors but SEM was not able to do that. SEM produced some valid cause and effect relationship [22] among the observed variables which will help us to understand the exact structure and mathematical relationship among them [Table No. 10].…”
Section: Discussionmentioning
confidence: 99%
“…Questionnaire A questionnaire study [10] was conducted on the study subjects. Factors included in questionnaire were: Socio-economic status of participant [ [11,12,22]. A model was accepted when all the criteria's were fulfilled;…”
Section: Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation